2011
DOI: 10.1017/s1049096511001247
|View full text |Cite
|
Sign up to set email alerts
|

Are Financial or Moral Scandals Worse? It Depends.

Abstract: Previous analysis finds that people respond differently to "financial" (e.g., tax evasion) and "moral" (e.g., sexual misconduct) political scandals. However, experimental and observational studies tend to reach different conclusions about which type of scandal induces a stronger negative reaction from the public. We use an experiment embedded in a national survey to examine the possibility that these divergent findings can, in part, be explained by a failure to consider the effects of abuses of power. Consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
101
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 14 publications
(28 reference statements)
2
101
1
Order By: Relevance
“…As such, there is no way to estimate a model predicting which allegations or transgressions become scandals, nor is it possible to directly estimate the effects of political and news context -which vary over time -in such a framework. 52 See, for example, Basinger 2013; Doherty, Dowling and Miller 2011;Funk 1996. including the presidential response strategies discussed by Basinger and Rottinghaus, are intermediate outcomes whose occurrence is likely to be endogenous. 53 Similarly, too few scandals exist under any reasonable definition to estimate an adequate statistical model of their duration.…”
mentioning
confidence: 99%
“…As such, there is no way to estimate a model predicting which allegations or transgressions become scandals, nor is it possible to directly estimate the effects of political and news context -which vary over time -in such a framework. 52 See, for example, Basinger 2013; Doherty, Dowling and Miller 2011;Funk 1996. including the presidential response strategies discussed by Basinger and Rottinghaus, are intermediate outcomes whose occurrence is likely to be endogenous. 53 Similarly, too few scandals exist under any reasonable definition to estimate an adequate statistical model of their duration.…”
mentioning
confidence: 99%
“…When others facilitate an unambiguously immoral behavior for political reasons, and all those involved are from the same party, a matter that previously seemed quite personal and easily contained can spread with signifi cant negative electoral repercussions. As Doherty, Dowling, and Miller (2011) argue, when moral scandals are coupled with abuses of offi ce, they can become powerful events. Previous studies, however, had not demonstrated that this combination could generate collective sanctions for other members of the same party.…”
Section: Discussionmentioning
confidence: 99%
“…If undeterred, repeated corruption scandals threaten to undermine the legitimacy of elections (Caillier 2010;Stockemer, LaMontagne, and Scruggs 2011;Villoria, Van Ryzin, and Lavena 2012). Surprisingly, the evidence from past studies is mixed as to whether politicians are punished more severely for corruption than other types of scandals (Doherty, Dowling, and Miller 2011). To be sure, corruption scandals are on average damaging to politicians (Basinger 2013;Hirano and Snyder 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Political cynicism may shape an individual's responses to these scandals (Dancey 2012). Certain types of scandal may affect public support differently than others and scandals that happened longer ago in time may have fewer consequences in declining approval than those that happened more recently (Doherty, Dowling and Miller 2011). Partisan politics plays a major role in the survival of scandal.…”
mentioning
confidence: 99%